2020
DOI: 10.1107/s1600577519014863
|View full text |Cite
|
Sign up to set email alerts
|

Methods for dynamic synchrotron X-ray respiratory imaging in live animals

Abstract: The imaging of live animals at a synchrotron source presents challenges in terms of remote monitoring and intervention, in addition to a sample that is changing and moving with time. This work describes experimental techniques that have been developed to address these challenges and capture image sequences that can equip a range of biomedical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 67 publications
(59 reference statements)
0
30
0
Order By: Relevance
“…It has been reported that addition of lung surfactant could facilitate pulmonary delivery both in terms of speed of dispersion and uniformity of distribution as surfactant is known to reduce surface tension of the applied bulk liquid . In this case, the mouse was intubated for syringe‐assisted slow‐instillation, but breathing spontaneously and in vivo X‐ray image acquisition (100 ms per breath) near the end of inhalation was triggered by monitoring the motion of the chest with an optical displacement sensor . In vivo PB‐PCXI revealed that delivery of 4 µL of iodine‐polystyrene NP liquid resulted in highly localized, small puddles of liquid into either the right or left lung, but not to both sides ( Figure a and Video S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that addition of lung surfactant could facilitate pulmonary delivery both in terms of speed of dispersion and uniformity of distribution as surfactant is known to reduce surface tension of the applied bulk liquid . In this case, the mouse was intubated for syringe‐assisted slow‐instillation, but breathing spontaneously and in vivo X‐ray image acquisition (100 ms per breath) near the end of inhalation was triggered by monitoring the motion of the chest with an optical displacement sensor . In vivo PB‐PCXI revealed that delivery of 4 µL of iodine‐polystyrene NP liquid resulted in highly localized, small puddles of liquid into either the right or left lung, but not to both sides ( Figure a and Video S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…As the X‐ray beam had a fixed horizontal orientation, mice needed to be positioned in a head‐high position. Therefore, mice were placed in a specially designed mouse holder on an x–y–z rotation stage to facilitate positioning in the X‐ray beam …”
Section: Methodsmentioning
confidence: 99%
“…As such, we are unable to offer any insights into the intra-breath alveolar and acinar dynamics, which could provide important insights into, for example, how the elastance of an individual alveolus is altered by VILI. Phase contrast synchrotron computed tomography offers a pathway to analyze alveolar dynamics in future studies ( Chang et al, 2015 ; Morgan et al, 2020 ). Another limitation is that the high inspiratory pressures and zero PEEP used to generate VILI in the current study are far outside clinical guidelines for safe ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…meter for the diagnosis of emphysema in a pre-clinical study with ex vivo mice (Schleede et al, 2012b). A detailed overview over the different methods for dynamic respiratory X-ray imaging with living animals has been given by Morgan et al (2020). As mentioned earlier, (differential) phase-contrast imaging provides improved soft-tissue contrast.…”
Section: Grating-based Phase-contrast Imagingmentioning
confidence: 99%